Raman and IR Spectroscopy Comlemented by Multivariate Alaysis as a Prospective tool to Investigate Biologically Relevant Materials - ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2018)
This talk will illustrate the use of Raman and infrared (IR) spectroscopies, complemented by other techniques (in particular chemometrics, but also thermodynamics methods. X-ray analysis and quantum chemical calculations) to address different problems related with biologically relevant materials. First, a methodology based on IR spectroscopy and principal component analysis (PCA) will be introduced for the analysis of blood plasma samples, in order to identify spectral changes correlated with biomarkers of schizophrenia and bipolarity. Then. Raman spectroscopy, complemented by several chemometrics approaches (e.g., PCA. cluster analysis) will be shown to be a powerful, practical and elegant tool to investigate composition (in particular the lipid/protcin ratio contents) of soybean strains. Specifically, the lipid/protcin ratio contents of salt-tolerant soybean mutants will be compared with those of control groups, and the changes induced by the mutations evaluated. Finally, results of a multidisciplinary investigation on the structural, spectroscopic, photochemical and thermal properties of a series of hydantoins will be presented. Hydantoins are a family of molecules that derive from imadazolidine and that are used commonly as pharmaceuticals (as anticonvulsive. anti-inflammatory, antiepileptic and anticanccr drugs, among other uses). The study addresses the properties of the isolated molecules of the investigated compounds and also those of their neat condensed phases, with emphasis to polymorphism.